PENYELESAIAN PERSELISIHAN HUBUNGAN INDUSTRIAL ANTARA PEKERJA KONTRAK PADA PT. SURVEYOR INDONESIA CABANG PEKANBARU MELALUI MEDIASI OLEH DINAS TENAGA KERJA DAN TRANSMIGRASI PROVINSI RIAU - Puspita, Rahmania; S, Thamrin; Febrianti, Lidia (Yayasan Pendidikan Islam Almatani, 2022)
Mediation is a dispute resolution outside the court that present a third party referred to as a mediator. The settlement of industrial relations disputes between contract workers and PT. Surveyor Indonesia Pekanbaru branch refers to law No. 2 of 2004 and the role of the mediator in the settlement of this dispute is considered quite good. Keywords :Work Termination, Industrial relations dispute, Mediation, The role of mediator